(untitled) (Revista Venezolana de Salud Pública, 2018)
The objectives of this work were the identification of a triatomine captured within a home located at 9 ° 17’2 "LN and 70 ° 25¨49" LO in the capital city of Trujillo State and the characterization of an entomopathogenic fungus found on the Integument and articulations of the captured specimen. For the isolation of the entomopathogen the insect was placed in a humid chamber for four days for a greater sporulation and for the development and isolation was used potato, Dextrose, Agar (PDA) culture medium. On the basis of the morphological characteristics of the specimen studied, these correspond to Rhodnius pictipes according to the pictorial key of triatomines (Hemiptera: Triatominae) from Venezuela. No eggs or nymphs were found inside the house to discuss possible colonization. As for the fungus, this was characterized as Beauveriabassiana whose characteristics are more noticeable its pattern of development of white color, turning to a yellowish coloration on the back of the plates, with conidiogenic globose to sub globose cells. In this work, we refer for the first time to the state Trujillo, Venezuela the invasion of Rhodnius pictipes to a house and its infestation with the entomopatógeno Beauveria bassiana.